Probing the in vivo biosynthesis of scytonemin, a cyanobacterial ultraviolet radiation sunscreen, through small scale stable isotope incubation studies and MALDI-TOF mass spectrometry - Jones, Carla S. (2011)
Scytonemin is a dimeric indole phenolic pigment found in the sheath of many cyanobacteria. This pigment absorbs UV radiation protecting subtending cyanobacterial cells from harmful effects. Based on scytonemin’s unique chemical structure, the pathway to its biosynthesis is uncertain, thus motivating the current investigation. Herein, we report the incorporation of both tyrosine and tryptophan into scytonemin, and provide in vivo data supporting the tryptophan origin of the ketone carbon involved in the condensation of the two biosynthetic precursors. This study also reports on the new use of a small-scale, MALDI-TOF mass spectrometry technique to monitor the incorporation of isotopically labeled tyrosine during scytonemin biosynthesis.